Can a Transport Model Predict Inverse Signatures in Lithium Metal Batteries Without Modifying Kinetics?. Issue 16 (29th December 2020) - Uppaluri, Maitri; Subramaniam, Akshay; Mishra, Lubhani; Viswanathan, Vilayanur; Subramanian, Venkat R.
Abstract : In this study, a one-dimensional transport model is developed and analyzed to predict the inverse overpotential signature observed during lithium metal electrodeposition. This simple approach predicts inverse signatures stemming from the competing interplay between moving boundary rates and mass transfer limitations. The numerical scheme used for the present model simulations is presented in detail which has been further used to study the effect of design parameters on the prevalence and strength of inverse signatures. It was found that the proposed model and the analysis is more pertinent to thick lithium symmetric cells, commonly used for in-depth fundamental studies.